(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study focuses on the effective use of dictionaries in German language lessons, highlighting their role in developing learners’ vocabulary and overall language skills. It explores practical methods for incorporating both monolingual and bilingual dictionaries into the classroom, aiming to enhance students’ lexicographic competence. The research discusses how guided dictionary use can improve understanding of word meanings, usage, and pronunciation, ultimately fostering autonomous learning. The paper also offers strategies for teachers to train students in efficient dictionary navigation and selection, tailored to various learning levels and contexts.